An experimental study on pre-stretched double-chamber 6000-series aluminium profiles subjected to quasi-static and dynamic axial crushing. (January 2021) - Qvale, Kristin; Hopperstad, Odd Sture; Reiso, Oddvin; Tundal, Ulf Håkon; Marioara, Calin Daniel; Børvik, Tore
Abstract: Automotive crash boxes require a material selection with strength and ductility in a balanced combination. In this work, the behaviour of double-chamber AA6063 and AA6082 aluminium profiles subjected to quasi-static and dynamic axial crushing was studied experimentally. The profiles were stretched to two different levels between extrusion and artificial ageing to temper T6. The higher pre-stretch resulted in a more ductile material with a slightly lower ultimate tensile strength. By visual inspection and by studying X-ray Computed Tomography scans of the tested profiles, dynamic loading was found to cause a larger amount of fracture than quasi-static loading. Highlights: Pre-straining the extrusions before artificial ageing results in higher ductility. Impact loading results in a higher mean force and a less ductile behaviour. CT scans of the deformed profiles were used to study fracture.